2016
DOI: 10.1515/cclm-2015-0807
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and the pathogenesis of menopause related disturbances and diseases

Abstract: Abstract:The postmenopausal phase of life is frequently associated in women with subjective symptoms (e.g. vasomotor) and real diseases (atherosclerosis with coronary ischemia, osteoporosis, Alzheimer-type neurodegeneration, urogenital dystrophy), which together determine the post-menopausal syndrome. Observations that oxidative damage by reactive oxygen/nitrogen species in experimental models can contribute to the pathogenesis of these disturbances stimulated research on the relationships between menopause, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 134 publications
(197 reference statements)
3
58
0
4
Order By: Relevance
“…Oxidative stress occurs when the production of free radicals exceeds the antioxidant capacity of the system. Free‐radical‐induced damage was considered to be a contributory factor in the development of insulin resistance, diabetes mellitus, and CVD . In the present study, high consumption of pro‐oxidant foods, including polyunsaturated fatty acids, refined carbohydrates, and sugars, was found among the women with MetS.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Oxidative stress occurs when the production of free radicals exceeds the antioxidant capacity of the system. Free‐radical‐induced damage was considered to be a contributory factor in the development of insulin resistance, diabetes mellitus, and CVD . In the present study, high consumption of pro‐oxidant foods, including polyunsaturated fatty acids, refined carbohydrates, and sugars, was found among the women with MetS.…”
Section: Discussionsupporting
confidence: 50%
“…Inflammation and oxidative stress both play important parts in the pathogenesis of MetS . In the present study, the C‐reactive protein levels were higher among the women with MetS than those without MetS.…”
Section: Discussionsupporting
confidence: 48%
“…Most of studies reported that the pathogenesis of osteoporosis is associated with oxidative stress in osteoblasts [2, 3]. Overproduction of ROS disrupts the balance between oxidation and antioxidant defense systems, leading to bone loss by promoting lipid peroxidation and lowering antioxidant enzymes, inducing apoptosis of osteoblasts and inhibiting bone formation [46].…”
Section: Introductionmentioning
confidence: 99%
“…En esta etapa, estos cambios en las mujeres pueden deberse a múltiples factores, uno de ellos es la formación de radicales libres o las especies reactivas del oxígeno (ERO) posiblemente debido a la disminución de las concentraciones de estrógeno circulantes en sangre periférica, los cuales bajan de 100-250 pg/mL, en la vida fértil, a 10 pg/mL (4) . Las bajas concentraciones de esta hormona pueden tener efectos prooxidantes, como, por ejemplo, ruptura del material genético, formación de aductos de ADN y oxidación de las bases (5) .…”
Section: Introductionunclassified
“…Frente a este problema, el organismo se protege utilizando sustancias denominadas "antioxidantes", los cuales son compuestos que detienen el ataque y la formación de radicales libres dentro de la célula (4,6) .…”
Section: Introductionunclassified